Culturas regionais e seus impactos na cultura organizacional: representação da matriz e de filiais - Barroso, Henrique César Muzzio de Paiva (2010)
This thesis analyzes the relationship of organizational culture with the Brazilian regional culture. Our assumption of regional differentiation is rooted in a literature that considers the cultural distinctions at the subnational level and its influence on the culture of organizations. The interest of our research focused on two main issues: 1) The organizational culture of a filial, which operates in a region of Brazilian culture different from their headquarters, moves away from the headquarters point of influence and also in relation to other filial? How the organization deals with it? 2) There is difference in values and practices between the headquarters and filial in other regions of Brazilian cultural and between the subsidiaries to each other in different regions? How the organization deals with it? In this sense, the objective of this research is to investigate a Brazilian business organization and its filial in different regions of Brazil in order to identify: 1) The differences between culture and organizational practices of the headquarters and the filial and between subsidiaries; 2) Differences in the relationship of the parent company and filial of other regions and how this influences the practices and organizational policies. To reach these goals, we rely on an interpretative epistemology research, exploratory and qualitative guidance, that used the research strategy the case study, using semi-structured interviews to compare the parent company and two filial from a food company, present in different regions of the country. The choice of a traditional company with national presence could illustrate the regional issue of our assumption, however, the data lead us to another direction. The moment the company is experiencing, which operated from a change in strategic focus, signals the importance of key aspects of organizational culture in transition which makes the regional issue important. We realized that the ancient culture has not led to a new data point to a cultural fragmentation, due to: 1) The diminishing importance of the founder, 2) The professionalization of management, 3) The progressive power transfer from Fortaleza to Sao Paulo, 4) The redirection to the consumer market, 5) The more complex control and more aggressive goals, 6) Reducing the autonomy of the units.